2014
DOI: 10.1200/jco.2013.50.3557
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan Synthase 3 Variant and Anthracycline-Related Cardiomyopathy: A Report From the Children's Oncology Group

Abstract: Hyaluronan (HA) produced by HAS3 is a ubiquitous component of the extracellular matrix and plays an active role in tissue remodeling. In addition, HA is known to reduce reactive oxygen species (ROS) -induced cardiac injury. The high cardiomyopathy risk associated with AA genotype could be due to inadequate remodeling and/or inadequate protection of the heart from ROS-mediated injury on high anthracycline exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(110 citation statements)
references
References 37 publications
2
98
1
1
Order By: Relevance
“…Broader genomic studies, using a platform directed at cardiovascular variants, identified that HAS3 predisposed to cardiomyopathy, most strongly in those exposed to higher anthracycline doses. 89 These findings illustrate the principle that pharmacogenetic risk factors may be highly dependent on the exact therapeutic regimen, with some genetic risk factors most evident at lower drug doses and others most evident at higher drug doses.…”
Section: Anthracyclinesmentioning
confidence: 94%
“…Broader genomic studies, using a platform directed at cardiovascular variants, identified that HAS3 predisposed to cardiomyopathy, most strongly in those exposed to higher anthracycline doses. 89 These findings illustrate the principle that pharmacogenetic risk factors may be highly dependent on the exact therapeutic regimen, with some genetic risk factors most evident at lower drug doses and others most evident at higher drug doses.…”
Section: Anthracyclinesmentioning
confidence: 94%
“…To our knowledge we investigated all reported SNP associated with ACT. However, three papers were published after genotyping had been performed: (i) Lubieniecka et al reported in a small pilot study in leukemia patients an association between daunorubicin-induced cardiotoxicity and P450 oxidoreductase polymorphisms, (ii) Blanco et al reported a role of polymorphisms in carbonyl reductase genes in childhood cancer survivors [16,17], (iii) Wang et al recently published an association of Hyaluronan synthase 3 variant with ACT in 93 children receiving anthracyclines [34].…”
Section: Discussionmentioning
confidence: 98%
“…Individual predisposition to anthracycline cardiotoxicity can also build on high expression levels of topoisomerase IIβ [60] or genetic variants of topoisomerase IIβ coregulating factors (retinoic acid receptor-γ) [61], polymorphisms of drug transporters that contribute to anthracycline distribution and elimination (ATP-binding cassette proteins of the multidrug resistance proteins family) [62], prooxidant enzymes (NADPH oxidase) [63], and matrix-remodeling enzymes (type 3 hyaluronan synthase) [64]. In brief, a constellation of factors may cause an unpredictable aggravation of cardiotoxicity.…”
Section: Primary Prevention Of Anthracycline Cardiotoxicitymentioning
confidence: 99%